Towards optimal nutritional care for all: A multi-disciplinary patient centred approach to a complex challenge. Issue 5 (May 2020) - de Man, Frank; Barazonni, Rocco; Garel, Pascal; van Ginkel-Res, Annemieke; Green, Ceri; Koltai, Tunde; Pichard, Claude; Roller-Wirnsberger, Regina; Sieber, Cornel; Smeets, Marcel; Ljungqvist, Olle
Summary: Ten years ago, European health care professional societies, health associations and members of the European Parliament convened in Brussels to discuss the necessary and urgent actions needed to improve access, initiation and follow up nutritional care for European citizens. As a response to this, in 2014 the Optimal Nutritional Care for All (ONCA) campaign was launched under the leadership of the European Nutritional for Health Alliance and its members. As of today this campaign has been rolled out in 18 European countries, whereby national multi-disciplinary platforms including patient groups work together to implement national nutritional care programs and develop good practices in care, research, education in order to increase awareness on malnutrition and improve nutritional care. This article describes the making of and evolution of the ONCA campaign, the outcomes and impact created, as well as opportunities to accelerate implementation of personalized nutritional care for all European citizens.